Feasibility and Safety of a New Chest Drain Wound Closure Method with Knotless Sutures - Kim, Min Soo (Korean J Thorac Cardiovasc Surg, 2018)
BACKGROUND: A method of wound closure using knotless suture material in the chest tube site has been introduced at our center, and is now widely used as the primary method of closing chest tube wounds in video- assisted thoracic surgery (VATS) because it provides cosmetic benefits and causes less pain. METHODS: We included 109 patients who underwent VATS pulmonary resection at Samsung Medical Center from October 1 to October 31, 2016. Eighty-five patients underwent VATS pulmonary resection with chest drain wound closure utilizing knotless suture material, and 24 patients underwent VATS pulmonary resection with chest drain wound closure by the conventional method. Complications related to the chest drain wound were compared between the 2 groups. RESULTS: There were 2 cases of pneumothorax after chest tube removal in both groups (8.3% in the conventional group, 2.3% in the knotless suture group; p=0.172) and there was 1 case of wound discharge due to wound dehiscence in the knotless suture group (0% in the conventional group, 1.2% in the knotless suture group; p=0.453). There was no reported case of chest tube dislodgement in either group. The complication rates were non-significantly different between the 2 groups. CONCLUSION: The results for the complication rates of this new chest drain wound closure method suggest that this method is not inferior to the conventional method. Chest drain wound closure using knotless suture material is feasible based on the short-term results of the complication rate.